Optical and EUV light curves of dwarf nova outbursts - Mauche, C; Mattei, J; Bateson, F (2001)
We combine AAVSO and VSS/RASNZ optical and Extreme Ultraviolet Explorer EUV light curves of dwarf novae in outburst to place constraints on the nature of dwarf nova outbursts. From the observed optical-EUV time delays of approximate to 0.75-1.5 days, we show that the propagation velocity of the dwarf nova instability heating wave is 3 km s(-1).